Being aware of the neurological manifestations of COVID-19 infection - Atalay, Basak (Faculty of Medicine, Universitas Trisakti, 2021)
The novel coronavirus disease- 2019 (COVID-19) is first reported from China, and unfortunately, no longer restricted, and spreads in all geographies.(1) The main symptoms of COVID-19 infection are respiratory tract related. Infected patients usually have symptoms such as fever, sore throat, and fatigue, and they may have atypical symptoms like headache, seizure, anosmia, stroke, and even impaired consciousness. Strong evidence of an association between COVID-19 infection and neurological manifestations has been reported. Besides, the neurologic manifestations may be the initial presentation of COVID-19 infection.